Answer:
Explanation:
4sin(x-π)cos(x-π) =√3
let (x-π) = (y)
2(2sin(y)cos(y)) = √3
sin(2y) = ½√3
2y = arcsin(½√3)
2y = ±π/3 + 2πn, ±2π/3 + 2πn
y = ±π/6 + πn, ±π/3 + πn
x - π = ±π/6 + πn, ±π/3 + πn
x = ±π/6 + π(n + 1), ±π/3 + π(n + 1)
As n = any whole number
x = ±π/6 + π(n), ±π/3 + π(1)
so in the range 0 ≤ x ≤ 2π
x = + π/6 + 0π = π/6
x = + π/6 + 1π = 7π/6
x = - π/6 + 1π = 5π/6
x = - π/6 + 2π = 11π/6
x = + π/3 + 0π = π/3
x = + π/3 + 1π = 4π/3
x = - π/3 + 1π = 2π/3
x = - π/3 + 2π = 5π/3
in increasing magnitude
x = π/6, π/3, 2π/3, 5π/6 7π/6, 4π/3, 5π/3, 11π/6